Pemberdayaan Ibu Tentang Pemberian Makan Bayi dan Anak Stunting Usia 6- 24 Bulan di Wilayah Kerja Puskesmas Wagir Kabupaten Malang - Apriyani Puji Hastuti; Hanim Mufarokha; Ratna Roesardhyati (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The community is expected to be able to play a role as actors in health development in maintaining, maintaining and improving their own health status and playing an active role in realizing public health. This hope is realized if it can empower communities and families, especially mothers in terms of feeding infants and children. This is very important because the mother in carrying out her role in the family provides food with sufficient nutrition for children as an ingredient in the process of growth and development. The problems found in the field are very complex related to toddlers. This is due to the availability of affordable access to nutritious food and the absence of easy early detection/screening tools to detect children who are experiencing malnutrition. The role of cadres in posyandu activities has not been maximized in terms of weighing weight, TB in posyandu activities and the role of cadres in providing supplementary food which is done every 2 weeks by the Puskesmas is not consumed by children but consumed by other family members. Families are expected to be able to prepare their children thoroughly so that children will have good adaptability in their environment. The role of the family in parenting has an important role, providing stimulation through games is a good thing to improve children's gross motor skills, fine motor skills, social independence and language. This family empowerment activity is an effort to increase promotive and preventive efforts to strengthen the quality of childcare with the target of family services, in addition to counseling and education in terms of strengthening the quality of care so that access can be utilized by all families in Indonesia. Solutions offered Seminars and training on infant and child feeding education and training on responsive feeding, Anthropometric measurements as a tool for measuring growth in children. The purpose of this community service activity is to increase the knowledge, willingness and skills of partners in terms of knowledge and skills regarding infants and children.